Teachers’ Readiness, Attitude, and Perceived Challenges Toward Generative AI Integration in Science Teaching - Diana Marce A. Valenciano; Lilibeth G. Abrogena (Future Science / FSH-PH Publications, 2026)
This descriptive research is focused on teachers’ level of readiness, attitude, and perceived barriers in Generative AI integration in science teaching. It was carried out in every public Junior High Schools under the Schools Division of Ilocos Norte (SDOIN). Through total enumeration, 160 science teachers who were at least three (3) years in the service during the School Year 2025-2026 were the respondents for this study. A survey questionnaire adapted from Alshorman, (2024), which employed a four-point Likert scale, was used as the research instrument to gather quantitative data on the level of readiness, attitudes, and perceived barriers. The data gathered were analyzed using weighted mean. Results revealed a high self-perceived competence in AI (M=3.10) and adequate access to resources (M=2.64). However, formal professional development remains a critical gap (M=2.42), with only 14.4% of respondents having attended AI-specific training. Teachers’ attitude toward Generative AI integration is high, signifying that they consider Generative AI to be helpful and useful in science teaching. In contrast, teachers perceive a high number of barriers in integrating Generative AI in science teaching. Overall, the findings emphasize the need for professional development and institutional support to address existing barriers and further strengthen the effective integration of Generative AI in science teaching.